Constraining Jumps in Density and Elastic Properties at the 660 km Discontinuity Using Normal Mode Data via the Backus‐Gilbert Method. Issue 9 (7th May 2021) - Lau, Harriet C. P.; Romanowicz, Barbara
Abstract: We apply the Backus‐Gilbert approach to normal mode center frequency data, to constrain jumps in P, S, bulk‐sound speed and density at the "660" discontinuity in the earth's mantle (∼650–670 km depth). Different 1‐D models are considered to compute sensitivity kernels. When using model PREM (Dziewonski & Anderson, 1981, Physics of the Earth and Planetary Interiors, 25, 297–356. doi:10.1016/0031‐9201(81)90046‐7) as reference, with a "660" at 670 km depth, the best‐fitting jumps in density, P‐ and S‐wave speeds range from (5.1–8.2)%, (5.3–8.0)%, (5.0–7.0)%, respectively, so the PREM values lie outside the ranges of acceptable density and P wave speed jumps. When shifting the depth of "660" to 660 km, the density and S wave speed jumps increase, while the P‐wave speed jump decreases. Normal mode data do not support a global transition at 650 km depth. The density jumps are closer to those of pyrolite than PREM, while our bulk‐sound wave speed jumps suggest a larger garnet proportion at "660." Plain Language Summary: Within the mantle, at around 650–670 km depth, rocks undergo a phase change due to an increase in temperature and pressure, from a relatively less dense mineral phase of ringwoodite to the denser phases of bridgmanite and periclase. This transition often marks the boundary between the upper and lower mantle. Switching between these two phases holds many dynamical consequences, when it comes to the convection of the mantle. We use low frequency seismic data known as normal modes, vibrations of the entire planet, to revisit the elastic and density properties of the mantle at this transition. We find that changes in the density and P‐wave speed across the boundary are different to what most standard seismic models have. We also find that the transition cannot be as shallow as 650 km. These conclusions bear consequences for those who research the convection and composition of the mantle and global seismologists. Key Points: We use recent normal mode center frequency data to constrain the elastic/density properties of the mantle 660 km discontinuity We find that acceptable range of jumps in P‐wave speed and density fall outside that of standard seismic reference models Our data preclude the global discontinuity being as shallow as 650 km depth